Maintenance Contract With Imperfect Preventive Maintenance - Hennie Husniah; B P Iskandar (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2015)
In this paper, we study performance based maintenance contracts for heavy equipment operated in a mining industry. A performance based service contract uses an attractive incentives to motivate the agent to increase the maintenance effort such that the resulting equipment’s performance is well above the target. This will in turn give benefits for both the owner of the trucks and the Agent of service contract. In this paper, we study performance based maintenance service contracts for the equipment sold with warranty and the perfomances considered includes availability and safety measures. We find the optimal strategy (i.e. price of each contract and maintenance effort) for the agent and the optimal option for the owner using a non-cooperative game formulation